Writing the Caribbean in magazine time - Seligmann, Katerina Gonzalez (Critical Caribbean studies., 2021)
"Writing the Caribbean in Magazine Time examines literary magazines generated during the 1940s that catapulted Caribbean literature into greater international circulation and contributed significantly to social, political, and aesthetic frameworks for decolonization, including Pan-Caribbean discourse. This book demonstrates the material, political, and aesthetic dimensions of Pan-Caribbean literary discourse in magazine texts by Suzanne and Aimé Césaire, Nicolás Guillén, José Lezama Lima, Alejo Carpentier, George Lamming, Derek Walcott and their contemporaries. Although local infrastructure for book production in the insular Caribbean was minimal throughout the twentieth century, books, largely produced abroad, have remained primary objects of inquiry for Caribbean intellectuals. The critical focus on books has obscured the canonical centrality of literary magazines to Caribbean literature, politics, and social theory. Up against the imperial Goliath of the global book industry, Caribbean literary magazines have waged a guerrilla pursuit for the terms of Caribbean representation"--